Food Choice Behavior With The Incidence Of Obesity In Adolescents School - Wahdaniyah Wahdaniyah; Nurfatwa Wilda Ningsi; Justiyulfah Syah (Jurnal Kesehatan Manarang, 2023)
Indonesia is in an epidemiological transition. On the one hand, there is still a problem of malnutrition, but on the other hand, obesity occurs. Increased prevalence of obesity from 15.3% in 2013 to 21.8% in 2018. This situation occurs due to a lack of physical activity and an unbalanced diet. This study aims to see the relationship of Food Choice behavior to the incidence of obesity. The population in the study is students in State Junior High School (SMPN) and State High School (SMAN) in Lembang Village in June 2023. The type of study used cross-sectional with a population of 1,398 adolescents. The purposive sampling technique was used with a sample of 94 adolescents. Data collection used the Food Choice Questionnaire (FCQ). The results showed that the most important reasons for food choice in adolescents with obese nutritional status were mood (4.00 ± 0.00), comfort (4.00 ± 0.00), and habits (4.00 ± 0.00). They had a significant relationship with each p-value = 0.00. The nutritional status of obesity is significantly related to the reasons for Food Choice on mood, comfort, and habits. Therefore, it is expected that related parties provide an understanding of the importance of choosing foods that can support health.